Coronavirus-Induced Host Cubic Membranes and Lipid-Related Antiviral Therapies: A Focus on Bioactive Plasmalogens - Deng, Yuru; Angelova, Angelina (Frontiers in Cell and Developmental Biology, 2021)
Coronaviruses have lipid envelopes required for their activity. The fact that coronavirus infection provokes the cubic membranes (CM) formation in host cells has not been rationalized in the development of antiviral therapies yet. In this context, the role of bioactive plasmalogens (vinyl ether glycerophospholipids) is not completely understood. These lipid species display a propensity for non-lamellar phase formation that facilitates membrane fusion, and modulate the activity of membrane-bound proteins such as enzymes and receptors. At the organism level, plasmalogen deficiency is associated with cardiometabolic disorders including obesity and type 2 diabetes in humans. A straight link is perceived with the susceptibility of such patients to SARS-CoV-2 (severe acute respiratory syndrome-coronavirus-2) infection and severe illness they suffered in addition to the difficulty in treatment. Based on correlations between the coronavirus-induced modifications of lipid metabolism in host cells, plasmalogen deficiency in the lung surfactant of COVID-19 patients, and the alterations of lipid membrane structure and composition including the induction of CM formation, we emphasize the key role of plasmalogens in the coronavirus (SARS-CoV-2, SARS-CoV or MERS-CoV) entry and replication in host cells. Considering that plasmalogen-enriched lung surfactant formulations may improve the respiratory process in severe infected individuals, plasmalogens can be suggested as an anti-viral prophylactic, a lipid biomarker in SARS-CoV and SARS-CoV-2 infections, and a potential anti-viral therapeutic component of lung surfactant development for COVID-19 patients.